No grown-ups allowed - Lewis, Beverly (Minneapolis, Minn. : Bethany House Publishers, 1995)
Jason takes advantage of his parents' absence to sneak forbidden chocolates behind his babysitting grandmother's back, but a Bible verse and a talk with God help him understand the importance of good behavior.
Keywords: Grandmothers; Christian life